A tale from the pit – educational work at the university. Issue 3 (3rd May 2016) - Erlandson, Peter
Abstract: Universities have their own particular ways of doing things. They have their own histories, their titles, their policy documents to attend to, and their own practices that have often evolved and taken form over centuries. The overall aim in this article is to illustrate an individual's complex growth into becoming a proficient university teacher from being a novice. With a phenomenological point of departure I analyze the embodied working conditions that a newcomer to university teaching carries around and gradually becomes familiar with – and even relatively proficient in – over a period of about three years. The focus in the article is the newcomer's reflective struggle with understanding her/himself and the social and cultural demands and possibilities that s/he is confronted with.